ANOMALOUS MAGNETIC FIELD ABOVE ANTICLINE STRUCTURES - HURA, K.; HRYSHCHUK, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Development of the mathematical expressions for computation of the magnetic field from anticline magnetic sources is examined. The plicate structures are related to the oil and gas deposits possibly. The results of calculation of the magnetic field are resulted for an anticline model.